Till' death (or conversion) do us part - Coptic divorces in Egyptian courts and their implications - Bishay, Barbara Viktoria (AUC Knowledge Fountain, 2010)
When President Gamal Abdel Nasser nationalized and unified the courts in 1956, he aimed at fostering unity and equality among the Egyptians. But this move has in fact achieved quite the opposite, as it forces Coptic Egyptians to sometimes choose between the freedom of practicing their religion and equality before the law, two basic human and civil rights that should be granted to all. By nationalizing the courts and yet still adhering to religious codes of personal status laws (PSL), legal dualism has not ceased to exist in Egypt and it is put into an ambivalent status between civil and Islamic state. Through these realities, the church becomes a state within the state of Egypt. This can be proven in the example of divorce, as two valid and at the same time contradicting judgments can and are issued in the exact same divorce case. This thesis combines historical studies of various kinds, such as on the court system in Egypt, on the countryâ s social and political history, on the relationship between the Egyptian state and the Coptic Orthodox Church as well as on the historical development of the Coptic canon laws since 1938. A historical basis and framework is thus provided for the analysis of Coptic divorces in connection to citizenship rights in contemporary times. As scholarship on contemporary divorce cases is extremely rare to non-existent, newspaper articles build the main reference and primary source for examining this issue. Continuous connections to the history of Coptic divorce laws as well as sectarianism in Egypt have been paid special attention to here, as they are of the utmost importance when analyzing contemporary Coptic divorce with its citizenship aspects. This thesisâ s findings prove the reality of legal dualism in Egypt, and that the Coptic Church has developed and inherited state-like qualities through this dualism, as well as through its relationship with the Egyptian state. Divorce becomes here an arena for negotiating not just citizenship but control over the Coptic laity and their private affairs. Both the church and the state enter this discourse with ambivalence and double standards, where both cannot seem to decide if they want Egypt to be a civil or an Islamic state. Citizenship for the Copts is limited by either side, when the Coptic citizen, who is looking to divorce, is put in the middle of the power struggles between these two forces and his two loyalties.